Statistical Evaluation of Green Economic Development Based on Rough Set Calculation Method. Issue 1 (August 2021) - Peng, Minjing; Fan, Jiajia
Abstract: In the context of big data, decisions and evaluations in business, economics and other fields increasingly rely on data analysis rather than experience and intuition. Data grows exponentially, but not all of it is useful. Rough set is a data mining method to deal with data classification, which can effectively remove redundant information. Green economy is an important proposition of the current world development. The evaluation of green economy should not only focus on economic data, but also environmental and social data. How to filter the data and establish a green economic index evaluation model is the problem this paper wants to solve. Based on the data of green economy and rough set algorithm, this paper evaluates the development level of green economy. Taking the data of Jiangmen city as an example, the evaluation model is tested and analyzed.